Specifications of the labor and material required in the construction of an Administration Building for the Kansas State Agricultural College, to be built at Manhattan, Kansas, in accordance with drawings and speciications prepared by R. H. Sanneman, Architect - Sanneman, Ramer Henry (My University, 1906)
Introduction: The work is to be executed under the direction and to the satisfaction of the building superintendent and in conformity with his instructions. The Contractor shall give his personal superintendence to the work, or have a competent foreman satisfactory to building superintendent in charge, on the job at all times to act for him, and shall furnish all materials, labor, etc., necessary to complete the work according to the true intent and meaning of the drawings and these specifications, of which intent and meaning the superintendent shall be the interpreter. No local terms or classification will be considered in the interpretation of these specifications. The location and grade of building will be indicated by the superintendent in charge, and the site shall be cleared by the contractor for the reception of the structure, and should be examined by him before bidding. The contractor must lay out his own work correctly and will be responsible for measurements. It is intended that the drawings and specifications shall include everything requisite and necessary to the proper and entire finishing of the building, notwithstanding every item necessary involved by the work is not particularly mentioned; and all work is to be delivered in perfect and undamaged state. Where no figures or memoranda are given, the drawings shall be accurately followed according to their scale. In any case of discrepancy in figures or drawings, the matter shall be submitted to the superintendent in charge, without whose decision said discrepancy shall not be adjusted by the contractor, save only at his own risk; and in the settlement of any complications arising from such adjustment, the contractor shall bear the expense involved. The drawings and these specifications shall be considered as co-operative, and work or materiel called for by the one and not mentioned in the other, is to be done or furnished as though fully treated of by both. The superintendent in charge may require the contractor to dismiss such workmen as he deems incompetent or careless, and is to have at all times access to the work, which is to be entirely under his control.
Citation: Sanneman, Ramer Henry. Specifications of the labor and material required in the construction of an Administration Building for the Kansas State Agricultural College, to be built at Manhattan, Kansas, in accordance with drawings and speciications prepared by R. H. Sanneman, Architect. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Architecture; Kansas State Agricultural College; Administration Building; Construction; Building Specificiations; Blueprints; Theses